2007
DOI: 10.1590/s1519-38292007000300010
|View full text |Cite
|
Sign up to set email alerts
|

Adequação da assistência pré-natal em gestantes atendidas em dois hospitais de referência para gravidez de alto risco do Sistema Único de Saúde, na cidade de Recife, Estado de Pernambuco

Abstract: OBJETIVOS: investigar a adequação da assistência pré-natal realizada por gestantes usuárias do Sistema Único de Saúde (SUS) da cidade do Recife, Pernambuco. MÉTODOS: estudo de corte transversal de 612 mulheres atendidas por ocasião do parto em duas unidades do SUS, referências para gravidez de alto risco no Recife, no período de junho a outubro de 2004. A avaliação do Pré-Natal foi baseada nos critérios do Programa de Humanização do Pré-Natal e Nascimento do Ministério da Saúde. RESULTADOS: a cobertura de pré-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
4
35

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 21 publications
1
12
4
35
Order By: Relevance
“…The number of six or more visits during PN was superior to several recent studies, which found 79.2% (1) 80.0 to 74.0% (15) , 80.0% (13) and 80.4% (16) , but lower than that of João Pessoa, with 89.9% (12) and Botucatu, with 94.0% in the FHSS and 97.0% in the traditional PHU (13) . Also, the combination of an early start of PN and conducting six consultations was higher than that found in two studies, one in São Paulo, at 63.1% (17) and another in Recife, at 38.0% (18) .…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The number of six or more visits during PN was superior to several recent studies, which found 79.2% (1) 80.0 to 74.0% (15) , 80.0% (13) and 80.4% (16) , but lower than that of João Pessoa, with 89.9% (12) and Botucatu, with 94.0% in the FHSS and 97.0% in the traditional PHU (13) . Also, the combination of an early start of PN and conducting six consultations was higher than that found in two studies, one in São Paulo, at 63.1% (17) and another in Recife, at 38.0% (18) .…”
Section: Discussioncontrasting
confidence: 55%
“…The number of six or more visits during PN was superior to several recent studies, which found 79.2% (1) 80.0 to 74.0% (15) , 80.0% (13) and 80.4% (16) , but lower than that of João Pessoa, with 89.9% (12) and Botucatu, with 94.0% in the FHSS and 97.0% in the traditional PHU (13) . Also, the combination of an early start of PN and conducting six consultations was higher than that found in two studies, one in São Paulo, at 63.1% (17) and another in Recife, at 38.0% (18) .The results suggest that the actions of the PHU for the involvement and adherence of pregnant women to followup throughout pregnancy are satisfactory, but need to be improved in order to increase the proportion of early start PN, combined with the minimum number of consultations recommended by the PHPB. The PHU in question provides healthcare services by way of the FHSS, which rearranges the care model in primary care, operationalized by way of the work of multidisciplinary teams responsible for a set number of families located in a defined geographical area.…”
contrasting
confidence: 54%
“…A maioria das pacientes foi internada no pós-parto (69,8%), o que é compatível com a literatura, que demonstra maior frequência de internamentos para terapia intensiva no puerpério (9) . …”
Section: Objetivounclassified
“…Em Recife/ PE, estudo revelou que somente 31% das mulheres referiram este procedimento em todas as consultas de pré-natal (13) . A avaliação ponderal propicia a detecção de possíveis patologias maternas que podem interferir negativamente no desenvolvimento fetal, como também no trabalho de parto, portanto, é relevante para todas as gestantes.…”
Section: Variáveis (N=196)unclassified
“…Esta porcentagem, apesar de alta, é preocupante, pois a palpação obstétrica é um dos pontos mais básicos a ser realizado durante o exame físico no pré-natal. Em Recife/PE, este procedimento foi mencionado por 42,1% das puérperas estudadas, como havendo sido realizado no mínimo duas vezes (13) . A avaliação de edema, que pode ser fisioló-gico ou patológico, foi citada somente por 101 (51,5%) entrevistadas.…”
Section: Variáveis (N=196)unclassified